Solar-induced 27-day modulation on polar mesospheric cloud (PMC), based on combined observations from SOFIE and MLS - Qiu, Shican; Yuan, Mengzhen; Soon, Willie; Velasco Herrera, Victor Manuel; Zhang, Zhanming; Yang, Chengyun; Yousof, Hamad; Dou, Xiankang (Frontiers in Astronomy and Space Sciences, 2023)
Temperature and water vapor are two key variables affecting the polar mesospheric cloud (PMC). Solar radiation can increase the mesospheric temperature through UV heating. In this paper, the composite solar index Y10 is used for the first time to study the influence of the solar radiation on PMC variability. The Ice water content (IWC) is selected to characterize the properties of PMCs. The observations of IWC are from the Solar Occultation For Ice Experiment (SOFIE) onboard the Aeronomy of Ice in the Mesosphere (AIM) satellite, and the temperature data used are measured by both SOFIE instrument and the Microwave Limb Sounder (MLS) onboard Aura satellite. According to the superposed epoch analysis (SEA) method, it is shown that the solar 27–day modulation can affect PMCs by changing and modulating the mesospheric temperature. The results show that the IWC responds to the Y10 later than the mesospheric temperature does. Further investigation of the relationship between mesospheric temperature and PMCs reveal that the average time lag is 0 days in the northern hemisphere (NH), and 1 day in the southern hemisphere (SH). The differences in temperature response to the 27–day solar rotational modulation with atmospheric pressure and latitude are also analyzed, based on the temperature observations from 2004 to 2020 by MLS. Twelve PMC seasons with 27–day periodicity are distinguished, 9 of which have temperature time lag decreased with increasing altitude because of the atmospheric dynamical effects.